"Es sahen dich die wasser - sie bebten..." (Ps 77:17b): die Funktion mytho-poetischer Sprache im Kontext von Psalm 77 - Weber, Beat (Old Testament essays, 2006)
The focus of this article is on the function and aim of the mythopoetic passage in Psalm 77: 17-20 - a psalm which probably reflects the fall of the northern kingdom. It will be argued that these verses do not constitute a later, secondary insertion, but were integrated into the psalm by the author himself (the compositioncritical model). The chiastic arrangement of vv. 16-21 links the salvation history and primordial kingship of YHWH deliberately in a "symbiotic" way. History and myth are two sides of the same coin. In Israel's time of crisis, the cosmic theophany is used to demonstrate the immediate power of God. The tension of Ps 77 is articulated in the last two verses: The Lord is present, stepping through the (chaotic) waters; but his way is also covered: God's footsteps are not recognisable. He leads his poeple through national leaders, whose functions are rooted in Moses and Aaron.